2010
DOI: 10.1037/2152-0828.1.s.36
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the form and function of self-injurious thoughts and behaviors: A real-time ecological assessment study among adolescents and young adults.

Abstract: Self-injurious behaviors are among the leading causes of death worldwide. However, the basic nature of self-injurious thoughts and behaviors (SITBs) is not well-understood because prior studies have relied on long-term, retrospective, aggregate, self-report assessment methods. We used ecological momentary assessment methods to measure suicidal and non-suicidal SITBs as they naturally occur in real-time. Participants were 30 adolescents and young adults with a recent history of self-injury who completed signal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
226
2
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(262 citation statements)
references
References 46 publications
(37 reference statements)
24
226
2
10
Order By: Relevance
“…Furthermore, NSSI acts were assessed with a single yes/no question. Although previous microlongitudinal work suggests that NSSI typically occurs on average one to three times total per week (Armey et al, 2011;Nock et al, 2009), it is possible that some days may have involved multiple instances of NSSI, which would not have been captured using the present assessment strategy. Finally, the current study was limited in its ability to examine how reactions to NSSI may differ depending on relationship type, as NSSI acts were almost exclusively revealed to romantic partners.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, NSSI acts were assessed with a single yes/no question. Although previous microlongitudinal work suggests that NSSI typically occurs on average one to three times total per week (Armey et al, 2011;Nock et al, 2009), it is possible that some days may have involved multiple instances of NSSI, which would not have been captured using the present assessment strategy. Finally, the current study was limited in its ability to examine how reactions to NSSI may differ depending on relationship type, as NSSI acts were almost exclusively revealed to romantic partners.…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge, very few studies have utilized such methods to examine the relationship between interpersonal experiences and NSSI. Using a micro-longitudinal study of self-injurious thoughts and behaviors among adolescents, Nock, Prinstein, and Sterba (2009) found that NSSI thoughts commonly began when adolescents were socializing; however, being alone (vs. with others) was a significant predictor of whether adolescents acted on these thoughts. Moreover, although interpersonal functions of NSSI were endorsed less frequently than intrapersonal functions of this behavior, both interpersonally oriented emotions (e.g., feeling rejected by and angry toward others) and intrapersonally oriented emotions (e.g., anger toward self, selfhatred) increased the odds of acting on NSSI thoughts .…”
mentioning
confidence: 99%
“…Two studies have shown the feasibility of electronic monitoring of suicidal ideation, using handheld computers [33,34]. Nock et al [33] used EMA to measure suicidal and non-suicidal self-injurious thoughts and behaviours as they occurred in real-time, demonstrating the feasibility of using EMA in this group.…”
Section: Ecological Momentary Assessment With Suicidal Patientsmentioning
confidence: 99%
“…Nock et al [33] used EMA to measure suicidal and non-suicidal self-injurious thoughts and behaviours as they occurred in real-time, demonstrating the feasibility of using EMA in this group. In Husky et al's study [34] the feasibility of EMA in four samples at varying risk for suicide (e.g., recent suicide attempters, past suicide attempters, affective controls and healthy controls) was determined.…”
Section: Ecological Momentary Assessment With Suicidal Patientsmentioning
confidence: 99%